PHONOLOGICAL AWARENESS AND LITERACY IN CHILDREN SHIPIBOS INITIAL LEARNING - Rojas Maynas, Jaico David (2019)
This research aimed to show that phonological awareness has a significant relationship with the initial reading in children shipibos of the Ucayali in the Peruvian Amazon region. A descriptive correlational model was applied to a sample of 31 students in the first grade of primary school. He was evaluated at the sample phonological awareness through a test that measured the dimension intrasilábica, syllabic and phonemic. To relate the obtained scores demonstrates the degree of Association of the dimension syllabic and intrasilábica phonological awareness with the initial training of the reading. Also confirmed that significant relationship with consciousness there is no phonemic in children shipibos of the 1st grade of primary education. The results confirm that the theoretical model of cognitive and psycholinguistic is a significant support of the reader learning. KEYWORDS: phonological awareness, learning to read, metalinguistic skills.